DETERMINANTS OF AUDITOR’S ABILITY TO DETECT FRAUD - Deliana, Deliana; Purba, Sadaukur Aeroki; Rahman, Abdul; Syahputra, Rizki; Sari, Eka Nurmala; Jamaludin, Mohd Faizal Bin (Kajian Akuntansi, 2024)
The study aims to provide empirical evidence on the effect of work experience, professional scepticism and time pressure on the ability of auditors to detect fraud. This research uses quantitative research methods that use statistical analysis tools, namely using Smart PLS (Partial Least Square) software. The data used is primary and comes directly from those surveyed, using a questionnaire designed to collect it. The questionnaires were distributed through the provision of paper questionnaires and through Google forms that were sent directly to the respondents. Sample in this study were 33 auditors in Medan City. The results of this study indicate that work experience positively affects the auditor's ability to detect fraud, while professional scepticism and time pressure do not affect the auditor's ability to detect fraud.             Keywords     : Ability to Detect Fraud, Professional Skepticism, Time Pressure, Work Experience.